Answer:
This is just multiplying not simplify.
Answer:
a = -12
b = -4
c = 4
d = 3
e = -3
Step-by-step explanation:
Answer:
y=-5/3x+13.
Step-by-step explanation:
As a line that is perpendicular to anoher line has a slope that is the negative reciprocal of the line's original slope, we know that the slope of our new line is -5/3. As it passes point (12, -7), we can use the point slope formula which is y-y1=m(x-x1). So plug in, y+7=-5/3(x-12) and that gives us y+7=-5/3x+20 which gives our final answer of y=-5/3x+13.
They have two different place values one 6 is in ten thousands place the other is in the hundred thousands place
The perpendicular slope is expressed as the negative reciprocal of the slope or − 1 m. In this scenario, the slope, or m, is −4 so the slope of the perpendicular line is − 1 −4 which simplifies to 1 4